The strategy of identity politics in the 2019 Indonesian presidential election in the era of the fourth industrial revolution - Ruchiandrean, Riffal (Journal of National Paradigm-Based Resilience Strategy, 2025)
Background: Identity politics plays a crucial role in shaping electoral strategies, particularly among millennials who are highly active on social media. This study explores three approaches to identity politics—Primordialism (personal characteristics and political background), Constructivism (self-image and credibility), and Instrumentalism (campaign management)—to assess their influence on the chances of victory in the 2019 Indonesian presidential election. Methods: The research applied a quantitative design using questionnaires as the main instrument. Data were collected from 300 millennial respondents who were active social media users and voted in the 2019 election. Logistic regression and factor analysis were employed to analyze the effects of the three approaches on electoral success. Findings: The results reveal that self-image, credibility, and campaign management have a significant positive effect on winning chances, while political background shows a significant negative effect. Personal characteristics did not significantly influence victory. The combination of constructivist and instrumentalist strategies proved most effective, yielding a winning opportunity value of 0.92. Conversely, primordialist strategies based on ethnicity, religion, or political background reduced electoral prospects. Conclusion: Constructivist and instrumentalist approaches are the most effective identity politics strategies to appeal to millennials and social media voters. Meanwhile, reliance on primordialist factors weakens electoral chances. Effective campaign management combined with a strong candidate image and credibility provides the best formula for electoral success. Novelty/Originality of this article: This study highlights the unique electoral behavior of millennials in the digital era, showing that image construction, credibility, and campaign management outweigh traditional primordial factors. It contributes to understanding how identity politics evolves in the context of social media-driven elections in Indonesia.